2018
DOI: 10.1097/ccm.0000000000002836
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Infusion Piperacillin-Tazobactam Decreases Mortality and Improves Outcomes in Severely Ill Patients: Results of a Systematic Review and Meta-Analysis*

Abstract: Receipt of prolonged infusion of piperacillin-tazobactam was associated with reduced mortality and improved clinical cure rates across diverse cohorts of severely ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 42 publications
5
72
0
1
Order By: Relevance
“…20,21 A systematic review and meta-analysis of 18 studies found prolonged piperacillin/tazobactam infusions were associated with reduced mortality and improved clinical cure rates in severely ill patients. 22 These findings mirror results from a large meta-analysis evaluating clinical outcomes in septic patients across a range of intravenous beta-lactams. 23 Prospective trials evaluating alternative beta-lactam regimens found mixed results, perhaps because of small sample sizes, diverse infections and causative pathogens, inconsistent dosing regimens, and heterogeneity or uncertainty of organism minimum inhibitory concentration (MIC).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…20,21 A systematic review and meta-analysis of 18 studies found prolonged piperacillin/tazobactam infusions were associated with reduced mortality and improved clinical cure rates in severely ill patients. 22 These findings mirror results from a large meta-analysis evaluating clinical outcomes in septic patients across a range of intravenous beta-lactams. 23 Prospective trials evaluating alternative beta-lactam regimens found mixed results, perhaps because of small sample sizes, diverse infections and causative pathogens, inconsistent dosing regimens, and heterogeneity or uncertainty of organism minimum inhibitory concentration (MIC).…”
Section: Discussionsupporting
confidence: 54%
“…While EI strategies improve the probability of pharmacodynamic target attainment in critically ill patients, various issues (eg, intravenous access, staff education, and transitions of care) create potential barriers to wider adoption . A systematic review and meta‐analysis of 18 studies found prolonged piperacillin/tazobactam infusions were associated with reduced mortality and improved clinical cure rates in severely ill patients . These findings mirror results from a large meta‐analysis evaluating clinical outcomes in septic patients across a range of intravenous beta‐lactams .…”
Section: Discussionmentioning
confidence: 83%
“…The target levels were most frequently missed in the q6 dosage regimen, presumably due to augmented renal clearance in those patients. For them, other dosing regimens like continuous infusion are necessary to achieve the target [50]. Richter et al reported higher rates of target attainment and reduced mortality in patients treated with continuous piperacillin infusion in contrast to a short infusion regimen [51].…”
Section: Discussionmentioning
confidence: 99%
“…However, evidence regarding the impact of target attainment on clinical effect remains limited in this population, and the data are inconsistent. In two recent systematic reviews and meta‐analysis, the authors identified a significant benefit in survival and clinical cure for prolonged infusion of β‐lactams compared with IA in critically ill patients. Conversely, Tamma et al .…”
Section: Discussionmentioning
confidence: 99%